Patient Satisfaction with Professional Continuous Glucose Monitoring in a Diverse Family Medicine Clinic: A Pilot Study - James E. Hougas, III; Heidi R. Nichol; Katherine Montag Schafer (University of Minnesota Libraries Publishing, 2022)
Primary care providers (PCPs) manage a large portion of patients with diabetes. Continuous glucose monitoring (CGM) can give detailed information about glucose trends to improve treatment and safety. We conducted a prospective cohort pilot study to understand patient experience with the use of professional CGM in a primary care practice with a high volume of diverse, non-English speakers. Eligible patients were on an insulin regimen and either had an A1c above goal or whose PCPs had concerns for hypoglycemia. Surveys were collected prior to the intervention to assess the acceptability of the patient's self-monitoring blood glucose efforts and after the intervention to assess their experience of using the CGM. Participants at baseline had a mean A1c of 10.6% and a high amount of emotional distress as measured on the Problem Areas in Diabetes (PAID) scale. Post-intervention, patients reported their experience with professional CGM was positive and, overall, as acceptable of an intervention as their previous self-monitoring blood glucose practice. Professional CGM can serve as an additional, acceptable tool for PCPs to better understand how to help patients achieve diabetes blood glucose goals. Ambulatory care pharmacists are well positioned to lead this effort in clinics.